Socio-Cultural Contradictions in the Development of the Regional Restaurant Services Consumer Market in Ukraine - Olha Danylenko; Maryna Bratitsel; Valerii Osiievskyi (Socio-Cultural Management Journal)
Introduction. The article explores the sociocultural contradictions accompanying the development of the consumer market of regional restaurant services in Ukraine. The purpose of the research is to identify the specific features shaping the consumption market of restaurant services across Ukrainian regions and to outline the key social and cultural contradictions that influence the formation of the typical consumer. The study employed general scientific methods of cognition: analysis, synthesis, generalisation, comparison, observation and a systems approach. The results demonstrate that conflicting interactions between rising consumer expectations, limited economic capabilities of businesses, and the realities of the cultural environment mark the development of the regional restaurant market. Emphasis is placed on the fact that the modern consumer seeks high-quality gastronomy and emotionally engaging cultural leisure that includes service, atmosphere, and personalised communication. In response to these shifts, there is an increasing demand for highly skilled staff capable of delivering the expected level of interaction. However, there is a noted shortage of trained professionals who can effectively operate under the communicative and psychological pressures of the restaurant industry. One of the critical sociocultural contradictions is the conflict between the drive to fully satisfy the customer and the need to maintain decent working conditions for staff. Excessive customer orientation, which often borders on indulging toxic behaviour, leads to a deterioration of the moral and psychological climate in teams, increased employee burnout, and disruptions in internal communication ethics. The study also examines the impact of the commercialisation of consumer relations on the expectations for individualised services, particularly in the context of dietary restrictions, ethical stances, and healthy lifestyles, which are not always compatible with the capabilities of a typical restaurant operation. Conclusions. Restaurateurs are forced to strike a balance between economic feasibility, cultural relevance, and the expectations of a new type of consumer – one who is informed, emotionally engaged, but often financially constrained. The practical value of the study lies in identifying problematic areas of sociocultural interaction within the restaurant industry, which may serve as a foundation for developing more effective management strategies in the hospitality sector.